Chemical Composition and Fermentation Characteristics of Different Proportions of Fermented Poultry Manure and Sheep Feces as Unconventional Feed - Aisy, Nadya Durrotul; Wardani, Arrynda Rachma Dyasti; Paradhipta, Dimas Hand Vidya; Agus, Ali; Noviadi, Cuk Tri (Jurnal Ilmu-Ilmu Peternakan, 2024)
The aim of this recent study was to investigate the effects of different ratios of poultry manure and sheep feces on the fermentation quality of fermented poultry and sheep manure (FPSM). This study used poultry manure, dry sheep feces, cassava flour, molasses, and the addition of multiple microbes (Saus Burger Pakan, SBP®). Dried and ground sheep feces, as adsorbents, were mixed with fresh poultry manure at different ratios, including 40% sheep feces and 60% poultry manure (T40), 50% sheep feces and 50% poultry manure (T50), and 60% sheep feces and 40% poultry manure (T60). Each treatment was replicated in triplicate, and 30 kg of each silo was fermented for 14 d. After fermentation, the samples from each treatment were analysed to determine their physical characteristics, chemical compositions, fermentation characteristics, and microbial contamination. The data were analysed using analysis of variance (ANOVA) followed by Duncan’s test if any significant difference was detected. The FPSM results showed that T60 presented (P<0.05) higher amounts of dry matter, crude fibre, pH, and lactic acid bacteria colonies. This study recommended the addition of as much as 60% SBP® inoculum and absorbent poultry manure to produce optimum and effective fermentation quality in poultry manure processing.